Bonding Social Capital’s Role in the Cooperative Development Based on Volunteer Through Social Innovation (Case Study: Koperasi Hutan Jaya Lestari, South Konawe) - Veritia; Chandra Fitra Arifianto (Publisher Cv. Inara, 2020)
Cooperatives are a form of social entrepreneurship. In addition to financial capital and human capital, social capital is an important factor for the sustainability of an organization. This case study aims to analyze the bonding social capital's role in cooperative development based on volunteers in KHJL, South Konawe, Indonesia. A qualitative approach was used in this study with the case study as a strategy for this research. The method of data collection is done by observing, interviewing, and studying documents. Interviews use semi-structured and in-depth. By using purposive sampling, there were eight persons to be interviewed. For the data validity and reliability to be optimal, the authors use triangulation in terms of primary and secondary data collection. Data analysis is done together, from the reduction to the presentation of the data, then there are conclusions and verification to create conclusions. It was found that the role of social capital especially trust plays an important role as bonding between members. For stakeholders, their role is continuously anticipated for the progress and development of cooperatives. Although currently, the cooperative's financial situation is not good, where timber customers have fallen dramatically and social innovation has not well worked yet. Trust in social capital is the main bonding for volunteers at KHJL, that's why KHJL is still surviving until now.